1999
DOI: 10.1108/00907329910303419
|View full text |Cite
|
Sign up to set email alerts
|

Assuring integrity of information utility in cyber‐learning formats

Abstract: Electronic networks are changing business operations worldwide. Universities must prepare students to handle the rapidly expanding range of commercial information in cyber formats. Although students can teach themselves to use technology, critical thinking skills are best acquired in a learning environment that encourages discussion and collaborative work. Faculty and librarians at the University of Delaware designed a cyber-learning project that combined discovery learning with problem-based learning. Teams o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…2 The new gadgets like the kindle, smart phones have become more popular for reading e-books. This has encouraged the availability of information in digital format in large scale 3 . The growing importance of ICT's, the internet, and the web has given a new dimension to the library and information centers 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 The new gadgets like the kindle, smart phones have become more popular for reading e-books. This has encouraged the availability of information in digital format in large scale 3 . The growing importance of ICT's, the internet, and the web has given a new dimension to the library and information centers 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Observations of the final reports showed that the assignment increased their ability to interpret the purpose of the data and articulate what they needed, and formed a strategy to collect the data better than they had when the data was already provided to them through course reserves. Discovery learning and problem-based learning in teams was the context for Morrison and Stein's (1999) interdisciplinary marketing class. They used a compare and contrast instruction activity to teach critical thinking about different modes of information sources.…”
Section: Instructional Methodsmentioning
confidence: 99%
“…He calls for replication in other courses and investigation into the effectiveness of a dedicated course in business information research. Morrison and Stein's (1999) assessment results of problem-based learning noted that the reliance on the single orientation instruction method cannot elicit the deep learning needed for critical evaluation of sources. In their instructional method they included team consultation with librarians as follow-up to the orientation sessions, yet students still rated ease of use as their primary criteria choice of tools.…”
Section: Recommendations For Further Research Extracted From Articlesmentioning
confidence: 98%
“…The worrying aspect is, consumers of information hardly look for the authenticity of the information they consume, which otherwise may be polluted to a greater degree and in many ways. Morrison & Stein (1999) in their study, while viewing their concerns about the information pollution, observed that more than 20% of all the future jobs will be involved in locating, assessing and checking the authenticity of the information to be consumed, and thereafter same shall be provided for consumption. Harris (1999) while highlighting the role and importance of information argues that information serves as the foundation in our lookout in understanding the world, be it by thinking, judgment or through our belief system.…”
Section: Introductionmentioning
confidence: 99%